2011
DOI: 10.3758/s13421-011-0164-2
|View full text |Cite|
|
Sign up to set email alerts
|

The role of stimulus type in list length effects in recognition memory

Abstract: While many studies have investigated the list length effect in recognition memory, few have done so with stimuli other than words. This article presents the results of four list length experiments that involved word pairs, faces, fractals, and photographs of scenes as the stimuli. A significant list length effect was identified when faces and fractals were the stimuli, but the effect was nonsignificant when the stimuli were word pairs or photographs of scenes. These findings suggest that the intrastimulus simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
146
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(155 citation statements)
references
References 49 publications
(125 reference statements)
6
146
3
Order By: Relevance
“…As we have mentioned previously, experiments with novel nonlinguistic stimulus classes uncovered small detrimental effects of list length and list strength, which are consistent with item noise models but inconsistent with context noise models (Kinnell & Dennis, 2012;. However, as noted by , the detrimental effects of list length and list strength were quite small in magnitude compared with what would be expected from a pure item noise model, and they suggested that both item noise and background noise are relevant to understanding recognition memory performance for nonlinguistic stimuli.…”
Section: Measuring Interference Contributions Within a Single Global supporting
confidence: 59%
See 4 more Smart Citations
“…As we have mentioned previously, experiments with novel nonlinguistic stimulus classes uncovered small detrimental effects of list length and list strength, which are consistent with item noise models but inconsistent with context noise models (Kinnell & Dennis, 2012;. However, as noted by , the detrimental effects of list length and list strength were quite small in magnitude compared with what would be expected from a pure item noise model, and they suggested that both item noise and background noise are relevant to understanding recognition memory performance for nonlinguistic stimuli.…”
Section: Measuring Interference Contributions Within a Single Global supporting
confidence: 59%
“…Kinnell and Dennis (2012) posited that the differences associated with the differ ent stimulus classes may be attributed to different levels of item noise, with word stimuli and natural scenes being exempt from item noise at retrieval whereas faces and fractals suffer from item noise, possibly because of having more distributed item representations (we return to the issue of how different stimulus classes can suffer from different degrees of item noise in the General Discussion). Included in the model fit are five experiments using the list length paradigm: the dataset of Dennis et al (2008) along with the four experiments by Kinnell and Dennis (2012). All of the exper iments use two list length conditions that all use a 1:4 list length ratio from the short list to the long list.…”
Section: Datasets Included In the Model Fitmentioning
confidence: 98%
See 3 more Smart Citations